Improving student problem-solving skill and cognitive learning outcome through the implementation of problem-based learning - Rusdi Hasan; Marheny Lukitasari; Vemy Juniarti; Irwandi Irwandi (Universitas Ahmad Dahlan, 2019)
Problem-solving is one of the competencies in the learning innovation that students must possess to prepare life challenges in the 21st century. This study aimed to improve student problem-solving ability and cognitive learning outcome through the implementation of problem-based learning (PBL) model in learning biology at the senior high school. This research is a quasi-experimental research with pretest and posttest design. Two classes were chosen randomly from five classes of 10th-grade students for conducting research by implementing PBL and direct instruction learning models as an experiment and control (conventional) class, respectively. The problem-solving ability was measured by the essay test as well as the cognitive learning outcome at the end of the research and was analyzed by t-test. The result showed that students in the PBL class have a higher improvement in problem-solving ability. The student ability to problem-solving in the PBL class was also significantly higher than the conventional class. In addition, students in the PBL class have a higher cognitive learning outcome than the conventional class. This finding indicates that the PBL model can be implemented in the learning practices, especially in biology, to develop the problem-solving skill of students.Problem-solving is one of the competencies in the learning innovation that students must possess to prepare life challenges in the 21st century. This study aimed to improve student problem-solving ability and cognitive learning outcome through the implementation of problem-based learning (PBL) model in learning biology at the senior high school. Thisresearch is aquasi-experimental research with pretest and posttest design. Two classes were chosen randomlyÂ from five classes of 10th-grade students for conducting research by implementing PBL and direct instruction learning models as an experiment and control (conventional) class, respectively. The problem-solving ability was measured by the essay test as well as the cognitive learning outcome at the end of the research and was analyzed by t-test. The result showed that students in the PBL class have a higher improvement in problem-solving ability. The student ability to problem-solving in the PBL class was also significantly higher than the conventional class. In addition, students in the PBL class have a higher cognitive learning outcome than the conventional class. This finding indicates that the PBL model can be implemented in the learning practices, especially in biology, to develop the problem-solving skill of students.